2011
DOI: 10.1016/s0140-6736(11)60779-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concurrent sexual partnerships on rate of new HIV infections in a high-prevalence, rural South African population: a cohort study

Abstract: SummaryBackgroundConcurrent sexual partnerships are widely believed to be one of the main drivers of the HIV epidemic in sub-Saharan Africa. This view is supported by theoretical models predicting that increases in prevalence of concurrent partnerships could substantially increase the rate of spread of the disease. However, the effect of concurrent partnerships on HIV incidence has not been appropriately tested in a sub-Saharan African setting.MethodsFor this population-based cohort study, we used data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(117 citation statements)
references
References 34 publications
(37 reference statements)
5
110
0
Order By: Relevance
“…Further, results in [5] showed that the proportion of men reporting that they have had 2 or more sex partners in a year ranged from 1% to 28% in sub-Saharan Africa. In other studies, [74] it was shown that the mean number of lifetime sexual partners ranged from 3.4 to 12.9 with a mean of 6.3 in sexually active men in the region. Mean lifetime number of partners of men in the immediate local community was predictive of hazard of HIV acquisition in women.…”
Section: Numerical Analysis and Resultsmentioning
confidence: 75%
“…Further, results in [5] showed that the proportion of men reporting that they have had 2 or more sex partners in a year ranged from 1% to 28% in sub-Saharan Africa. In other studies, [74] it was shown that the mean number of lifetime sexual partners ranged from 3.4 to 12.9 with a mean of 6.3 in sexually active men in the region. Mean lifetime number of partners of men in the immediate local community was predictive of hazard of HIV acquisition in women.…”
Section: Numerical Analysis and Resultsmentioning
confidence: 75%
“…Meeting sex partners in hospitality-settings was also associated with a history of having a high number of female partners, and relatively higher number of kathoey partners, which is an important finding given multiple sexual partnerships increase the risk of transmission of HIV and other STIs (Tanser et al, 2011). In contrast, U.S.-based studies have identified associations between meeting sex partners on the Internet and through sex-on-premises venues and reporting a higher number of sex partners (Grov et al, 2013;Horvath et al, 2006;Xia et al, 2006).…”
Section: Discussionmentioning
confidence: 88%
“…But even behavior change interventions targeted at reducing multiple partnering more generally are difficult to bring about; indeed it is unclear that anyone knows how to do this. There is a possibility that messaging targeted specifically on concurrent partnerships could be harmful, by leading to less focus on other forms of multiple partnering, and by negatively impacting on those forms of concurrency which are in fact protective Rosenthal, 2010a, 2010b;Tanser et al, 2011). Further, messaging which implies differences in African sexuality may provoke damaging and even deadly reactions, such as the dissidence of Thabo Mbeki, and therefore must be used with circumspection.…”
Section: Resultsmentioning
confidence: 99%
“…A widely accepted, relatively recent hypothesis is that a primary driver is a particular model of sexual partnering, referred to as 'multiple concurrent partnerships' or 'concurrency' (Epstein and Halperin, 2007;Epstein and Morris, 2011;Mah and Shelton, 2011). Lively debate about this explanation is ongoing, with serious questions raised as to whether it is supported by evidence Rosenthal, 2010a, 2010b;Padian and Manian, 2011;Sawers and Stillwaggon, 2010;Tanser et al, 2011). We discuss two problems with the concurrency explanation.…”
Section: Introductionmentioning
confidence: 91%